Structured fault information-aided canonical variate analysis model for dynamic process monitoring. (April 2023) - Lou, Siwei; Wu, Ping; Yang, Chunjie; Xu, Yonghong
Abstract: Process monitoring is one of the most crucial fundamental components in industrial processes. Traditional multivariate statistical analysis modeling only relies on data collected in normal condition, reflecting the lack of sensitivity to faults. This paper proposed a fault information-aided canonical variate analysis (FICVA) and a structured FICVA (SFICVA) monitoring strategy to improve fault detection rate. In FICVA, canonical variate analysis (CVA) is firstly applied to extract state and residual subspace based on normal data. Then, according to the data collected from one fault, the above subspaces are further decomposed into fault relevant and irrelevant state subspaces, and fault relevant and irrelevant residual subspaces for guaranteeing fault information can be concentrated. The correlation between normal data in various subspaces and the ability to concentrate abnormal information in fault data from fault relevant subspaces are theoretically analyzed. Then, to combine diverse fault information from different scenarios, SFICVA monitoring strategy is performed through Bayesian inference to ensemble a series of FICVA sub-models constructed by different faults to obtain more effective performance. Through a numerical example, experimental research on Tennessee Eastman process (TEP) and actual blast furnace ironmaking process (BFIP), rationality of FICVA method and effectiveness of SFICVA monitoring strategy are fully verified. Graphical abstract: Highlights: We proposed a FICVA method by constructing fault relevant and irrelevant subspaces. Theoretical is analyzed, such as Information correlation and concentration ability. SFICVA is proposed and constructs comprehensive statistical indicators. Numerical case, TEP and BFIP show improved sensitivity and monitoring performances.